2019
DOI: 10.1111/hel.12565
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth supplements as the first‐line regimen for Helicobacter pylori eradication therapy: Systemic review and meta‐analysis

Abstract: Background and Aims An increase in the use of antibiotics leads to increased antibiotic resistance of Helicobacter pylori (H pylori). Consequently, it has been considered that the first‐line standard regimen should be changed. The main purpose of this study was to evaluate the efficacy of nonantibiotic (bismuth) supplements as a first‐line regimen for H pylori eradication. Methods We searched PubMed, EMBASE, CINAHL, and the Cochrane Library databases for randomized controlled trials (RCTs) reported in English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 49 publications
0
52
0
7
Order By: Relevance
“…Many studies have shown that among different combinations of bismuth-based quadruple therapy, the success rate can exceed 90%. [28][29][30] Ko et al 31 also showed that when the studies were performed in a high clarithromycin-resistant area (≥15%) or included patients with clarithromycin resistance, bismuth-containing regimens were superior to non-bismuth regimens. The advantage of bismuth quadruple therapy was that its efficacy was not affected by antibiotic resistance, while dual resistance to CLA and MET >15% impaired the efficacy of all non-BQTs.…”
Section: F I G U R E 2 Cyp2c19 Polymorphism Detected In Patients a mentioning
confidence: 99%
“…Many studies have shown that among different combinations of bismuth-based quadruple therapy, the success rate can exceed 90%. [28][29][30] Ko et al 31 also showed that when the studies were performed in a high clarithromycin-resistant area (≥15%) or included patients with clarithromycin resistance, bismuth-containing regimens were superior to non-bismuth regimens. The advantage of bismuth quadruple therapy was that its efficacy was not affected by antibiotic resistance, while dual resistance to CLA and MET >15% impaired the efficacy of all non-BQTs.…”
Section: F I G U R E 2 Cyp2c19 Polymorphism Detected In Patients a mentioning
confidence: 99%
“…Bismuth-containing quadruple therapy exhibits a high eradication rate, even in the presence of antibiotic resistance. 3 Although resistance rate to metronidazole is over 30% in Korea, bismuth-containing quadruple therapy is effective unless the minimum inhibitory concentration (MIC) of metronidazole exceeds 32 μg/mL. 4 Furthermore, H. pylori resistance against tetracycline has been low and stable in Korea for the past 16 years.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of bismuth to clarithromycin based triple therapy has been shown to increase the eradication rate. 38 One can consider addition of bismuth to triple therapy but more data are needed to establish its incremental value in Singapore.…”
Section: Challenges and Future Strategiesmentioning
confidence: 99%